Estimating the volume of water losses in the irrigation industrial crops project in Aziziyah district and ways to raise its efficiency - Ayad A. Ali Salman Al-Shammery/ natiq hashim tufan alshamry/ Najah A. Owayez Al-Ghasham ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The research dealt with a geographical study of the industrial crops project located on the left bank of the Tigris River in the district of Aziziyah, as it is one of the large irrigation projects that irrigates an agricultural area of ​​20,000 acres, extending for a distance of 37 km. The natural and human characteristics of the study area, and the importance of the project in terms of agricultural, industrial and marketing terms, and its important economic role have been exposed. The research reviewed a number of manifestations and negative effects of the project’s water losses, including the formation of swamps and ponds, the salinization of the lands adjacent to the project and the expansion of the environmental pollution of the area, as well as the lack of water shares for the lands on the outskirts. The reasons for the occurrence of waste from the project water were also investigated, which were mainly represented by the process of leaching and evaporation, and an attempt was made to calculate the amount of wasted water and then estimate the efficiency of the irrigation project and suggest some solutions to help reduce or reduce those losses. DOI /10.54633/2333-021-042-007